Extraction of Nitric Acid, Americium(III), Curium(III), and Lanthanides(III) into DMDOHEMA Dissolved in Kerosene. Issue 7 (9th November 2020) - Geist, Andreas; Berthon, Laurence; Charbonnel, Marie-Christine; Müllich, Udo
ABSTRACT: Liquid-liquid distribution data were determined for the extraction of nitric acid, Am(III), Cm(III), and lanthanides(III) from 0.1–7 mol/L nitric acid into 0.5–1 mol/L N, N' -dimethyl- N, N' -dioctyl-2-[2-(hexyloxy)ethyl]-malonamide (DMDOHEMA) dissolved in kerosene. Nitric acid extraction was accurately modeled accounting for the adducts (HNO3 )L2, (HNO3 )L, and (HNO3 )2 L. To model Am(III) extraction, the following complexes were taken into account, Am(NO3 )3 L4, Am(NO3 )3 (HNO3 )L3, and a third complex, Am(NO3 )3 (HNO3 )2 L3 (considering spectroscopic results) or Am(NO3 )3 (HNO3 )2 L2 (considering slope-analysis results). Separation factors for Am(III) over Cm(III) and the lighter lanthanides(III) are practically independent of nitric acid concentration. Am(III)/Ln(III) separation factors decrease with increasing nitric acid concentration for the heavier lanthanides(III).